Verification of Legal Acquisition under the CITES Convention: The Need for Guidance on the Scope of Legality. Issue 3 (3rd July 2019) - Korwin, Sebastien; Denier, Louisa; Lieberman, Susan; Reeve, Rosalind
Abstract: The two main prerequisites for legal international trade under CITES are the non-detriment finding, or NDF, in which a scientific authority certifies that the export of a given Appendix I or Appendix II species will not be detrimental to the survival of the species in the wild, and verification by the Management Authority that species are not being traded in contravention of the laws of that state for the protection of fauna and flora. This is referred to as a legal acquisition finding, or LAF. Verifying legal acquisition through an LAF is a fundamental requirement of CITES and underpins the legitimacy of the entire system of international trade under the Convention. When an international shipment of specimens of CITES-listed species is accompanied by a permit, it is seen as certification by the exporting country that the shipment is legal in every sense. However, it is widely recognised that this obligation is implemented inconsistently, leading to illegally acquired CITES-listed species entering the market and undermining the credibility and effectiveness of CITES permits. This inconsistent implementation is partly due to differing understanding of what can reasonably be said to constitute laws "for the protection of flora and fauna, " i.e., the scope of legality of legal acquisition verifications under CITES. This article explores the scope of legality of legal acquisition verifications under CITES as well as recent developments leading to the adoption of guidance on Legal Acquisition Findings at the 18th Conference of the Parties (CoP18) in August 2019. It draws from the experience of the EU Forest Law Enforcement Governance and Trade (FLEGT) process, whose understanding of legality extends beyond the scope of laws directly related to the extraction and trade of timber to include laws pertaining to environmental quality, biodiversity conservation, land tenure (access and ownership), and other considerations relevant to the long-term sustainability of trade in a natural resource such as timber. The article argues that there is much to be gained from establishing a collaborative process within CITES to develop a shared understanding of the range of laws that ought to be considered and complied with when determining legal acquisition, ultimately contributing to better implementation of CITES.